2022
DOI: 10.1186/s12864-022-08399-7
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptomic responses of blunt snout bream (Megalobrama amblycephala) to acute hypoxia stress alone, and in combination with bortezomib

Abstract: Background Blunt snout bream (Megalobrama amblycephala) is sensitive to hypoxia. A new blunt snout bream strain, “Pujiang No.2”, was developed to overcome this shortcoming. As a proteasome inhibitor, bortezomib (PS-341) has been shown to affect the adaptation of cells to a hypoxic environment. In the present study, bortezomib was used to explore the hypoxia adaptation mechanism of “Pujiang No.2”. We examined how acute hypoxia alone (hypoxia-treated, HN: 1.0 mg·L− 1), and in combination with bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 95 publications
2
11
0
Order By: Relevance
“…Based on RNA‐seq data, we found that the DE mRNAs encoding the enzymes involved in the TCA cycle ( sdh , fh , and mdh ) were significantly downregulated and the DE mRNAs encoding the enzymes involved in glycolysis ( hk1 / hk2 , pfk , gapdh , pk , and ldh ) were clearly upregulated, and these genes were also differentially down‐ or upregulated at the remaining time points under hypoxia. Similar results have been reported for large yellow croaker 7,43 . These results suggested aerobic respiration was inhibited and a rapid adaptive activation of anaerobic ATP‐generating pathway under hypoxia stress.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Based on RNA‐seq data, we found that the DE mRNAs encoding the enzymes involved in the TCA cycle ( sdh , fh , and mdh ) were significantly downregulated and the DE mRNAs encoding the enzymes involved in glycolysis ( hk1 / hk2 , pfk , gapdh , pk , and ldh ) were clearly upregulated, and these genes were also differentially down‐ or upregulated at the remaining time points under hypoxia. Similar results have been reported for large yellow croaker 7,43 . These results suggested aerobic respiration was inhibited and a rapid adaptive activation of anaerobic ATP‐generating pathway under hypoxia stress.…”
Section: Discussionsupporting
confidence: 88%
“…In tilapia ( Oreochromis niloticus ), changes in glucose, lipid, and amino acid metabolism quickly occurred to hypoxia exposure 11 . Similar results were observed in rainbow trout ( Oncorhynchus mykiss ), 12 , 13 large yellow croaker ( Larimichthys crocea ), 14 and blunt snout bream ( Megalobrama amblycephala ) 7 . Besides, hypoxia stress also influenced immune responses of fish.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Transcriptomic studies have been conducted about hypoxic stress in many fish species. In blunt snout bream ( Megalobrama amblycephala ) liver tissue, KEGG pathway enrichment analysis found that these differentially expressed genes (DEGs) were enriched in HIF-1, FOXO, MAPK, PI3K-Akt and AMPK signaling pathway ( Zhao et al, 2022 ). While in another Cyprinidae fish, silver carp ( Hypophthalmichthys molitrix ), KEGG enrichment analysis found a similar pattern that PI3K-Akt, FOXO and JAK-STAT were among most prominent pathway activated by hypoxia in heart tissue ( Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using these techniques, researchers have unraveled a series of molecular changes in fish under hypoxic stress. It has been reported that in channel catfish (Ictalurus punctatus) [16] and blunt snout bream (Megalobrama amblycephala) [17], the pathways significantly enriched with differentially expressed genes (DEGs) under hypoxic stress are HIF-1, MAPK, and PI3K-Akt. The environmental stress caused by hypoxia reduces the oxygen transfer to the surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%